Effect of Season on Physico-Morphological Attributes of Cryopreserved Hariana Bull Spermatozoa - Singh, Vipin; Kumar, Anuj; Yadav, Chhote Lal; Patel, Akhil; Yadav, Brajesh; Saxena, Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was undertaken to evaluate the effect of seasonal variations on various seminal attributes and freezability of Hariana bull semen. The study was conducted over a period of four months and divided into two peak seasons as winter (December-January) and summer (May-June). Twenty-four ejaculates were collected from 4 bulls in each season. The physico-morphological characteristics of semen, viz., volume (ml), mass activity (0-5 scale), pH, sperm concentration (million/ ml), progressive motility (%), sperm livability (%), HOST (%), total morphological sperm abnormality (%) and acrosomal integrity (%) were estimated at different stages of cryopreservation in different seasons. During summer season the ejaculate volume and seminal pH were found non-significantly higher than in winter, whereas the percentage of morphologically abnormal spermatozoa was significantly (p
Keywords: Freezability, Season; Semen; Hariana bull.